Membangun komunitas yang egaliter: Analisis sosio-kultural tentang persoalan Onesimus dalam Filemon 1:8-22 - Bastian, Yonas; Aryanto, Antonius Galih Arga Wiwin (KURIOS, 2023)
This research paper about Onesimus attempts to analyze the letter of Philemon by employing historical-critical methods, especially approaching the problem of Onesimus in the context of Roman Slavery in the first century. The approach highlights the status of Onesimus as a slave who runs away from his master, Philemon. According to Roman Law, Onesimus must be punished for his position as a fugitive. In his letter, Paul desires to solve the problem between the slave and his master in the context of a Christian relationship. He beseeches Philemon to accept Onesimus back, not as a slave but as a brother in Christ. In the Greco-Roman community, Paul teaches the community to get one another as brothers and sisters because of their baptism. Although the members have different social statuses, including slave and master, Jewish and Greek, man and woman, all of them are united in the same faith in Christ. Paul’s letter to Philemon becomes a pastoral encouragement emphasizing love as the foundation for Christian life and strengthening the community to forgive and accept one another.AbstrakPaper penelitian tentang Onesimus ini bertujuan untuk menga-nalisis teks Filemon menggunakan metode historis kritis dengan melaku-kan pendekatan pada persoalan Onesimus dari konteks sosial budaya ten-tang sistem perbudakan Romawi di abad pertama. Pendekatan itu mem-perjelas status Onesimus sebagai seorang budak yang melarikan diri dari tuannya, Filemon. Berdasar hukum Romawi, Onesimus harus dihukum karena menjadi fugitivus. Dalam suratnya, Paulus berusaha menyelesai-kan persoalan relasi budak dan tuannya ini dalam sebuah relasi jemaat Kristiani. Paulus meminta Filemon untuk menerima kembali Onesimus bukan hanya sebagai budak, tetapi juga sebagai saudara dalam Kristus. Dalam komunitas yang kental dengan budaya Romawi itu, Paulus meng-ajar mereka untuk menerima sesamanya sebagai saudara karena pembap-tisan yang sama. Meskipun anggota jemaat memiliki perbedaan status sosial termasuk tuan dan budak, orang Yahudi dan orang Yunani, laki-laki dan perempuan, mereka disatukan dalam iman yang sama akan Kristus. Surat kepada Filemon menjadi anjuran pastoral Paulus yang menekankan kasih sebagai dasar hidup Kristiani dan mendorong komunitas untuk sa-ling mengampuni dan menerima satu sama lain.